O turismo e a dinâmica intra-urbana de Caldas Novas(GO): uma análise da expansão e reestruturação do complexo hoteleiro - Paulo, Renata Ferreira Calado de (2005)
This work ha as objective to analyze the intra-urban dynamics of Caldas Novas, caused by the amplification and restructuring of the hotel complex happened mainly in the end of decade of 1990. Great part of the works writings on Caldas Novas, they bring a study about the thermal waters and the use of the same ones. But an analysis of the urban and tourist growth starting from the exploration of that thermal water table, was not still made. For so much, reading of referring works about that subject, direct our researches and, were visited to the questionnaires and interviews were applied to the contractor of the hotel branch an population, respectively, what a lot aided us in the obtaining or qualitative data. We had the opportunity to know the dynamic tourist population closely and also the tourists opinion and of the resident population in the city about the tourism. We analyzed the vertical building process, essential in the reproduction of the urban soil and construction of present heterogeneous spaces in the city. The analysis the artificial public spaces also permeated our studies. Fruit of the intense exploration of the urban soil, the artificial space the urban atmospheres, being the same addressed to the tourist taste that goes by the city. We verified that the intra-urban dynamics in differentiated in the periods of larges and less tourist movement. The periods considered low season, for they are less attractive, they receive less tourists, while the periods of high season, that is to say, lingering holidays an vacations are more favorable and attractiveness for the practice of the tourism. This dynamic heterogeneous popularity is one of the responsible factors for the space, economic and tourist transformations for which the city is passing now.